2010
DOI: 10.1111/j.1471-4159.2010.06759.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‐1 mediates prostaglandin E2 elevation and contextual memory impairment in a model of sustained hippocampal interleukin‐1β expression

Abstract: J. Neurochem. (2010) 114, 247–258. Abstract Interleukin (IL)‐1β is a proinflammatory cytokine implicated in several neurodegenerative disorders. Downstream actions of IL‐1β include production of prostaglandin (PG) E2 by increasing expression of cyclooxygenase (COX) enzymes and prostaglandin E synthase (PGES) isoforms. We recently developed a transgenic mouse carrying a dormant human IL‐1β eXcisional Activation Transgene (XAT) for conditional and chronic up‐regulation of IL‐1β in selected brain regions. This mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 53 publications
3
51
0
Order By: Relevance
“…However, the COX-1-specific inhibitor SC-560 was also protective against acute cognitive dysfunction, and reduced hippocampal and thalamic PGE 2 concentrations, while the COX-2-specific inhibitor NS-398 did not afford protection against the LPS-induced working memory deficits and did not reduce the disease-induced elevation in brain PGE 2 levels. Recent studies inducing chronic hippocampal overexpression of IL-1␤ also showed that COX-1 was chronically elevated (Ն2 months) and was involved in inflammation-mediated cognitive change (Matousek et al, 2010), and it is known that direct infusion of PGE 2 into the brain can induce working memory deficits (Matsumoto et al, 2004) and impair contextual fear conditioning (Hein et al, 2007). The results presented here suggest that levels of COX-1-dependent prostaglandins are elevated in diseased animals and cause a vulnerability to working memory deficits when subsequently exposed to mild-to-moderate inflammation.…”
Section: The Inflammatory Route To Deliriummentioning
confidence: 99%
“…However, the COX-1-specific inhibitor SC-560 was also protective against acute cognitive dysfunction, and reduced hippocampal and thalamic PGE 2 concentrations, while the COX-2-specific inhibitor NS-398 did not afford protection against the LPS-induced working memory deficits and did not reduce the disease-induced elevation in brain PGE 2 levels. Recent studies inducing chronic hippocampal overexpression of IL-1␤ also showed that COX-1 was chronically elevated (Ն2 months) and was involved in inflammation-mediated cognitive change (Matousek et al, 2010), and it is known that direct infusion of PGE 2 into the brain can induce working memory deficits (Matsumoto et al, 2004) and impair contextual fear conditioning (Hein et al, 2007). The results presented here suggest that levels of COX-1-dependent prostaglandins are elevated in diseased animals and cause a vulnerability to working memory deficits when subsequently exposed to mild-to-moderate inflammation.…”
Section: The Inflammatory Route To Deliriummentioning
confidence: 99%
“…There exist two genetically distinct isoforms of the cyclooxygenases: COX1 and COX2. COX1 is in general a constitutive enzyme, but has been demonstrated to be upregulated during certain inflammatory conditions (Schwab et al, 2000;Shukuri et al, 2011;Anrather et al, 2011;Matousek et al, 2010). The COX2 gene on the other hand has several transcriptional regulatory sites in its promoter and can be induced by various pro-inflammatory cytokines.…”
Section: Prostaglandin E2 Synthesis and Receptorsmentioning
confidence: 99%
“…mPGES1 is the main isomerase responsible for inflammation induced PGE2 (Jakobsson et al, 1999). Studies have suggested that mPGES1 primarily couple to COX-2 over COX1, but other findings demonstrate exceptions to this rule, and mPGES1 has been found to couple to COX1 in cases where the concentration of arachidonic acid is high (Matousek et al, 2010;Chandrasekharan et al, 2005;Murakami et al, 2000). COX2 provides the main source of prostaglandin E2 production mediating inflammatory symptoms such as fever and loss of appetite (Wilhelms et al, 2014;Nilsson et al, 2017a) and in particular endothelial mPGES1 is important for the pyrogenic response to inflammation (Ek et al, 2001;Engblom et al, 2003;Wilhelms et al, 2014).…”
Section: Prostaglandin E2 Synthesis and Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…17) In spite of co-induction of mPGES-1 and COX-2 in the same cells, evidence for distinct signaling pathways leading to mPGES-1 and COX-2 induction was observed in a study where phosphatidylinositol 3-kinase inhibition effectively uncoupled co-regulation of these two enzymes in rat microglia treated with lipopolysaccharide (LPS).…”
Section: Microsomal Prostaglandin E Synthase-1mentioning
confidence: 99%